Buckling resistance of compression members with back‐to‐back connected angle sections. Issue 2 (1st September 2021) - Beyer, André; Bureau, Alain; Jaspart, Jean‐Pierre
Abstract: This paper focusses on the buckling resistance of compression members made of back‐to‐back connected angle sections. The studied built‐up members are connected through bolted packing plates. Due to the flexibility of this connection, these members generally do not fully work as a single member but the connection stiffness has to be accounted for. In Eurocode 3 Part 1‐1 it is currently admitted to neglect the effect of the connection stiffness if the packing plates possess a maximum distance of 15 imin (imin is the minimum radius of gyration of one individual angle section, also called "chord"). Elsewise the influence of the packing plates on the member resistance should be accounted for. The limit distance of 15imin appears to be much lower than the past practice, consequently leading to a more conservative design and a complexification of the fabrication. This paper therefore presents a sensitivity analysis focusing on the influence of several parameters as: the distance of packing plates, the presence of clearance in bolt holes and the influence of preloaded bolts. These parameters are studied with a numerical model based on solid finite elements. Owing to the use of solid elements, it is possible to model explicitly the bolts, the packing plates and all contact regions.